2022
DOI: 10.1140/epjd/s10053-022-00494-4
|View full text |Cite
|
Sign up to set email alerts
|

QED effects at grazing incidence on solid-state targets

Abstract: New laser facilities will reach intensities of $$10^{23} \text {W cm}^{-2}$$ 10 23 W cm - 2 . This advance enables novel experimental setups in the study of laser–plasma intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…At the end of 2022, one of the team members was invited to the International Scientific Conference -75 th Jubilee of the Institute of Art History and Archaeology of the Ss. Cyril and Methodius University in Skopje, and presented a new hoard of bronze jewellery from the vicinity of Požarevac, whose inventory indicates possible influences and imports in the Braničevo region (Filipović and Jacanović 2022). Further data will be available following the analysis of samples that have been sent to the laboratory.…”
Section: Towards Better Comprehension and Visibility Of Resultsmentioning
confidence: 99%
“…At the end of 2022, one of the team members was invited to the International Scientific Conference -75 th Jubilee of the Institute of Art History and Archaeology of the Ss. Cyril and Methodius University in Skopje, and presented a new hoard of bronze jewellery from the vicinity of Požarevac, whose inventory indicates possible influences and imports in the Braničevo region (Filipović and Jacanović 2022). Further data will be available following the analysis of samples that have been sent to the laboratory.…”
Section: Towards Better Comprehension and Visibility Of Resultsmentioning
confidence: 99%
“…Filipovic and Pukhov investigate QED effects when high-intensity laser pulses graze the surface of a solid-state target by two-dimensional particle-in-cell simulations [ 5 ]. It is shown that the electrons extracted from the solid target collide with the counter-propagating laser, which can trigger several QED effects and lead to a QED cascade under a sufficiently high laser intensity.…”
mentioning
confidence: 99%